The Sense of the Past : Essays in the History of Philosophy - Williams, Bernard, 1929-2003 (Book collections on Project MUSE., 2006)
Before his death in 2003, Bernard Williams planned to publish a collection of historical essays, focusing primarily on the ancient world. This posthumous volume brings together a much wider selection, written over some forty years. His legacy lives on in this masterful work, the first collection ever published of Williams's essays on the history of philosophy. The subjects range from the sixth century B.C. to the twentieth A.D., from Homer to Wittgenstein by way of Socrates, Plato, Aristotle, Descartes, Hume, Sidgwick, Collingwood, and Nietzsche. Often one would be hard put to say which part i.